The Effect of Selecting Government Expenditure and Unemployment on The Human Development Index in Indonesia - Primambudi, Ganjar (Proceeding Universitas Muhammadiyah Yogyakarta Graduate Conference, 2020)
Purpose of the study: Human resources are an important aspect of national development. Indonesia's large population can be an advantage and also boomerang if not managed properly. In fact, there are still many provinces that have a human development index (HDI) below the national average. On the other hand, government spending in various sectors continues to increase every year. This study aims to analyze the effect of unemployment and various selecting government expenditure variables to HDI. It is necessary to identifying these factors so the government can make decisions quickly to accelerate HDI. Data and Methodology: The data in this study use time series on an annual basis from the Ministry of Finance and Indonesia BPS period 2010-2019. The dependent variable is human development index. The independent variables are unemployment, government spending on education and health. The method of this study is the descriptive and quantitative approach with multiple linear regression analysis tools Eviews 10.0. Findings and Novelty: Variable education and health expenditure have a positive and significant impact on HDI with regression coefficient values of 0.007621 and 0.031969. While the variable unemployment has a negative impact but not significant on HDI with a regression coefficient of -0.279214. Government expenditure in education and health effectively increase the HDI due to education and health aspect contribute to the level of knowledge and life expectancy. While unemployment does not have too much impact on HDI because the majority of unemployed people in Indonesia are in the affluent category with education in the middle level